2020
DOI: 10.3390/su13010297
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Potential Evapotranspiration Using Temperature-Based Heuristic Approaches

Abstract: The potential or reference evapotranspiration (ET0) is considered as one of the fundamental variables for irrigation management, agricultural planning, and modeling different hydrological pr°Cesses, and therefore, its accurate prediction is highly essential. The study validates the feasibility of new temperature based heuristic models (i.e., group method of data handling neural network (GMDHNN), multivariate adaptive regression spline (MARS), and M5 model tree (M5Tree)) for estimating monthly ET0. The outcomes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 75 publications
(92 reference statements)
2
12
0
Order By: Relevance
“…Wen et al (2015),Mehdizadeh et al (2017), andAdnan et al (2021) confirm that, overall, the soft computing approach performs better than empirical equations, which is in agreement with the present study finding. Furthermore,Mehdizadeh et al (2017) reported the strong ability of SVM-polynomial in estimating monthly ETo in Iran.…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Wen et al (2015),Mehdizadeh et al (2017), andAdnan et al (2021) confirm that, overall, the soft computing approach performs better than empirical equations, which is in agreement with the present study finding. Furthermore,Mehdizadeh et al (2017) reported the strong ability of SVM-polynomial in estimating monthly ETo in Iran.…”
supporting
confidence: 92%
“…The GMDH-NN model has the ability to handle several inputs variables and predict a single output, using different layers in the model. Each layer output considers an input to the next layer (Adnan et al 2021). The GMDH-NN's layer structure can be presented as:…”
Section: Group Methods Of Data Handling Neural Network (Gmdh-nn)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the advent of soft computing tools, developments in data-driven models using metaheuristic algorithms have been incorporated to model various hydrological processes. The most common meta-heuristic algorithms are support vector machine (SVM) [2,8,10], random tree (RT), artificial neural networks (ANNs), M5 pruning tree (M5P) [2,16,17], reduced error pruning tree (REPTree), multivariate adaptive regression splines (MARS) [2,13,16], extreme learning machine (ELM), gene expression programming (GEP), and random subspace (RSS). Furthermore, their hybrids with a variety of algorithms have been efficiently used to estimate pan evaporation [14,18,19].…”
Section: Introductionmentioning
confidence: 99%